The consumer protection movement and the effects of Law 19.496 - Mendoza H., Miguel (Estudios de Administración, 1999)
The contents review the evolution of the consumers' protection movement in Chile and over the world. The subject matter is set forth in terms of the various normative bodies enforced in different countries and regions in the course of time. A theoretical frame is proposed in order to evaluate the consumers' protection movement from three perspectives: the State, through legal enforcement, regulation and education; consumers' organizations, by recourse to education and information to the public, and enterprises, through competition, self-regulation and education. Reference is also made to the possible sources of the development and importance that the consumers' protection movement is evidencing in many countries nowadays. The contents search into the empirical evidence in Chile, in the light of the existing consumers' protection law and its impact on the national scene. The conclusion reached is that the probability to obtain satisfaction upon submission of a complaint has decreased ever since the enforcement of the current law. Empirical evidence supports the hypothesis that activities including a considerable service component are the most affected by consumers' dissatisfaction.